Effectiveness of Problem-Based Learning to Students’ Problem-solving and Critical Thinking Skills: A Systematic Review - Gabrielito Garil (Journal of Education, Management and Development Studies)
The effectiveness of PBL in various fields has been explored for the past decades – in medical schools, higher education schools, and even in K-12 schools. However, its effectiveness relative to students' problem-solving and critical thinking skills remains narrow, mainly in K-12 secondary schools. Moreover, only a few studies have focused on this concern over the last decade. Therefore, this systematic review aims to study the effectiveness of PBL alone and against the conventional model in terms of students' problem-solving and critical thinking skills in secondary school. The study utilized the PICO (Population, Intervention, Comparison, Outcome) Concept to frame the research questions, followed the seven stages of the Systematic Approach, and employed the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) Protocol in selecting and analyzing the ten primary resources generated from online databases such as Google Scholar and Semantic Scholar. The resources showed similar quantitative methodology in investigating the effectiveness of PBL at such a level of education. Overall, the analysis shows that 100% of the studies indicated that PBL significantly impacts the students' problem-solving and critical-thinking skills and should be applied in teaching and learning. Furthermore, it is recommended that an extensive, similar study be conducted and possibly include more academic resources to investigate this learning model's actual effectiveness further.